CXCL9-Derived Peptides Differentially Inhibit Neutrophil Migration In Vivo through Interference with Glycosaminoglycan Interactions - Vanheule, Vincent; Boff, Daiane; Mortier, Anneleen; Janssens, Rik; Petri, Björn; Kolaczkowska, Elzbieta; Kubes, Paul; Berghmans, Nele; Struyf, Sofie; Kungl, Andreas J.; Teixeira, Mauro Martins; Amaral, Flavio Almeida; et al. (Frontiers in Immunology, 2017)
Several acute and chronic inflammatory diseases are driven by accumulation of activated leukocytes due to enhanced chemokine expression. In addition to specific G protein-coupled receptor (GPCR)-dependent signaling, chemokine – glycosaminoglycan (GAG) interactions are important for chemokine activity in vivo. Therefore, the GAG – chemokine interaction has been explored as target for inhibition of chemokine activity. It was demonstrated that CXCL9(74-103) binds with high affinity to GAGs, competed with active chemokines for GAG binding and thereby inhibited CXCL8- and monosodium urate (MSU) crystal-induced neutrophil migration to joints. To evaluate the affinity and specificity of the COOH-terminal part of CXCL9 towards different GAGs in detail, we chemically synthesized several COOH-terminal CXCL9 peptides including the shorter CXCL9(74-93). Compared to CXCL9(74-103), CXCL9(74-93) showed equally high affinity for heparin and heparan sulfate (HS), but lower affinity for binding to chondroitin sulfate (CS) and cellular GAGs. Correspondingly, both peptides competed with equal efficiency for CXCL8 binding to heparin and HS but not to cellular GAGs. In addition, differences in anti-inflammatory activity between both peptides were detected in vivo. CXCL8-induced neutrophil migration to the peritoneal cavity and to the knee joint were inhibited by intravenous or intraperitoneal injection of CXCL9(74-103) or CXCL9(74-93), but not CXCL9(86-103), with similar potency. In contrast, neutrophil extravasation in the MSU crystal-induced gout model, in which multiple chemoattractants are induced, was not affected by CXCL9(74-93). This could be explained by (1) the lower affinity of CXCL9(74-93) for CS, the most abundant GAG in joints, and (2) by reduced competition with GAG binding of CXCL1, the most abundant ELR+ CXC chemokine in this gout model. Mechanistically we showed by intravital microscopy that fluorescent CXCL9(74-103) coats the vessel wall in vivo and that CXCL9(74-103) inhibits CXCL8-induced adhesion of neutrophils to the vessel wall in the murine cremaster muscle model. Thus both affinity and specificity of chemokines and the peptides for different GAGs and the presence of specific GAGs in different tissues will determine whether competition can occur. In summary, both CXCL9 peptides inhibited neutrophil migration in vivo through interference with GAG interactions in several animal models. Shortening CXCL9(74-103) from the COOH-terminus limited its GAG-binding spectrum.